Effect of the ground-state structure on order parameters in ±J Ising lattices - Ramirez Pastor, Antonio Jose (2004)
The Edwards-Anderson site order parameter, q, or its generalizations have been considered to study the partial spin-glass behavior of ±J Ising lattices. These parameters vanish if all 2W ground states are taken into account, so an ergodic separation must be done in order to emulate nature. Here, we follow a recently proposed criterion to do ergodic separation in spin glasses. The method relies upon: (i) the complete knowledge of the physical properties of the ground level and (ii) a new algorithm to calculate the diluted lattice that remains after removing all bonds that frustrate in any of the ground states. With this new methodology, reproducible values of the order parameters have been obtained. Size effects and tendency towards the thermodynamic limit are established.